ANALISA CACAT PENYUSUTAN MATERIAL FCD450 DAN ALUMINIUM A356 PADA PROSES PENGECORAN STANG PISTON DINDING TIPIS MENGGUNAKAN SIMULASI - Cahaya, Nicolas Hary; Yamin Lubis, Sobron; Riza, Abrar (POROS, 2023)
Metal castings are generally used to manufacture machine parts with complex shapes, including the manufacture of thin wall components. Thin wall casting (TWC) is a casting method for producing lightweight component objects by thinning the component walls such as plates or parts of the cast object that can be thinned. Thin wall ductile iron (TWDI) is nodular cast iron, casted through TWC. TWDI makes nodular cast iron possible to compete with aluminum when compared to the weight between these two materials. The application of aluminium to TWC aluminum will lead to lighter components production. The main reason aluminum is replacing cast iron in the automotive field is the inability or lack of interest on the part of cast iron manufacturers to produce lightweight iron components, which is TWDI. The use of simulation in the casting process helps to show the whole process in casting. This research was conducted to determine the effect of using the TWC design made for nodular cast iron on aluminum and the defects formed by using this design through software simulation. The casting design used uses Sulamet-Ariobimo et al. casting design [10] which has succeeded in producing connecting rod components using TWDI on an industrial scale. The simulation software used is the Altair Inspire Cast simulation (serial number: 680344) owned by PT. Wisma Teknik Lestari. Simulations were carried out for both FCD450 and A356 materials. Based on the results of the shrinkage simulation, there are shrinkage defects in the TWDI material and there are no shrinkage defects in Aluminum A356. This is due to the solidification characteristics and cooling rate of the two materials, where the cooling rate for TWDI is 3.84E+4 J, and 8.85E+4  J for Aluminum A356. In addition, based on the solid fraction simulation results, there are hotspots on cast components for TWDI materials which result in shrinkage defects in the components